Benzodiazepines use in elderly patients attended at a Public Pharmacy in Pernambuco Brazil - Freitas, Eliane da Silva; Diniz, Joaquim Alves; Alves, Natália Rodrigues; Leite, Pedro Ivo Palacio; Rolim Neto, Modesto Leite; Carvalho, Poliana Moreira Medeiros de (Amadeus International Multidisciplinary Journal, 2019)
: The elderly people are the group that most use psychotropic drugs, due to psychiatric comorbidity and somatic conditions. In Brazil some benzodiazepines are part of the National List of Essential Medicines (RENAME) being distributed free of charge, facilitating the population access, which can lead to irrational use. Methods: Cross-sectional, descriptive research through a qualitative and quantitative study of benzodiazepine use in patients attended at the Cedro Basic Pharmacy in the city of Cedro-PE. The data collection was done with the application of a semi-structured questionnaire. The pattern of benzodiazepine use has been described through patient-reported symptomatology, therapeutic adherence, medical specialty, dose increase without medical consultation, and adverse effects reported during the drug use. Results: There was a predominance of females (58.33%). The most commonly used benzodiazepine was diazepam (66.67%). The purchase of benzodiazepine without a prescription was reported by 16.67% of the elderly interviewed and an increase in the drug dose without doctor consulting by 25% of the interviewees. Final considerations: The prescription of these drugs for the elderly, as well as the chronic use, should consider the physiological changes caused by aging and the adverse effects of these drugs in order to guarantee a safe treatment. Keywords : Aged; Psychotropic drugs; Drug utilization.